PROFIL KEMAMPUAN KOGNITIF SISWA DALAM MENYELESAIKAN SOAL IDENTITAS TRIGONOMETRI KELAS X-1 SMA NEGERI 1 JAYAPURA BERDASARKAN GAYA BELAJAR - Fitriani, Fitriani (Universitas Pendidikan Mandalika (UNDIKMA), 2017)
This study aims to determine the profile of cognitive abilities of high school students in solving trigonometric identity problems based on learning styles. The level of cognitive ability in this research is to remember, understand, apply, analyze, evaluate, and create, while learning style used is visual learning style, auditorial learning style, and kinesthetic learning style. Based on the purpose of this type of research is descriptive research with kulaitatif approach. Subjects in this study were X-1 students of SMA Negeri 1 Jayapura which amounted to 3 people. Subjects taken were one subject with visual learning style, one subject with auditorial learning style, and one subject with kinesthetic learning style, the selection of this subject using purposive sampling technique. The data were collected by using questionnaire of learning style, written test, and interview. Based on the results of research subjects with visual learning styles have the ability to cognitive remember, understand, apply, analyze, evaluate and create. Subjects with auditorial learning style have cognitive abilities to apply and evaluate. subjects with kinesthetic learning styles have a cognitive ability to understand, apply, and evaluate. Learning styles are not the only factors that influence the different cognitive abilities of each subject. Teachers, individual abilities, and the state of the learning environment also influence the differences in cognitive abilities in each subject. The ability of teachers to create diverse learning strategies can develop students' cognitive abilities even when teachers teach in the classroom with students who have different learning styles.